The Rosie Project - Graeme Simsion
Love isn't exact science - but no one told Don Tillman. A handsome thirty-nine-year-old geneticist, Don's never had a second date. So he devises The Wife Project, a scientific test to find the perfect partner. Enter Rosie - 'the world's most incompatible woman' - throwing Don's sage, ordered life into chaos. Just what is this unsettling, alien emotion he's feeling?